Poetic Identity and Mindful Literacy in EFL Classroom: A Way to Invent Freedom in Language Learning - Kadek Sonia Piscayanti; Entika Fani Prastikawati; Lorie Mae Coloquit (Universitas PGRI Semarang, 2026)
The research of poetic identity and mindfulness in EFL context has been an impactful wave in recent years. The learning explores how the students reveal and construct their identity in the form of poetry. Poetry is the representation of deepest voices in the personal context of the learners. With mindful learning, the learners achieve their personal freedom to express their deepest voices. Through this mindfulness-based poetic identity learning in EFL poetry classroom, a personal point of view is deeply investigated through the poetry. This is qualitative research which explores the combined methodology of poetic identity of Iida’s theory, narrative inquiry, and poetry theory. The subject were 28 students in poetry class who were taught in mindfulness-based learning with focus on poetic identity writing and narrative inquiry, equipped with poetry journal assessment. The findings reveal that poetry could elevate meaning making, respect deepest voices, builds language identity, and boosts language authenticity. This research deepens the perspectives that literacy learning can be best taught by mindfulness-based learning and poetic identity writing, through which freedom in language learning is experienced and sensed in the meaningful way.